Investigation of the MMP1 and MMP3 promoter polymorphisms in temporomandibular joint disorder [Temporomandibular baǧlantı bozukluklarnda MMP1 ve MMP3 promotor polimorfizmlerinin incelenmesi] - (:unkn) unknown (Halic Universitesi Fen-Edebiyat Fakultesi, 2011)
Matrix metalloproteinases 1 and 3 (MMP1 and MMP3) are metal dependent endopeptidases responsible for hydrolyzing extracellular matrix molecules, and also have important roles during the matrix destruction in temporomandibular joint (TMJ) degeneration. In the present study, we aimed to investigate the relation between characterized promotor polymorphisms of MMP1 and MMP3 genes and TMJ in a Turkish population. 35 TMJ patients and 50 healthy controls were recruited to the study. MMP1 and MMP3 promotor polymorphisms were examined by PCR-RFLP methodology. For MMP1 polymorphism; 8, 14 and 13 of 35 patients were 1G/1G, 1G/2G and 2G/2G, respectively. For the same polymorphism; 11, 28, 11 of 50 controls were 1G/1G, 1G/2G and 2G/2G, respectively. 6, 14, 15 of 35 patients were 5A/5A, 5A/6A and 6A/6A, respectively, for MMP3 genotype. Of the 50 controls, 8, 23, 19 were 5A/5A, 5A/6A and 6A/6A, respectively. Comparison of the polymorphism between healthy subjects and patients yielded no statistically significant difference (p>0,05). The examined polymorphisms didn't have major effects on the TMJ formation. With the increasing number of the both groups and classification of the patients with their pain level and disease severity will give us more informative data about the polymorphism of the genes and TMJ formation.
Keywords: Matrix metalloproteinase; MMP1 promotor polymorphism; MMP3 promotor polymorphism; Orofacial pain; Temporomandibular joint disorder